Scaling pathways for sustainable intensification in the polders of coastal Bangladesh - A seven-year journey - International Rice Research Institute (International Rice Research Institute, 2023)
This video captures the unique ecosystem of the polders and its stakeholders who work together to improve the agricultural productivity in the Bangladesh coastal zone for climate resilience and prosperity.